2017
DOI: 10.1007/s10681-017-1869-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation for nitrogen use efficiency traits in current and historical great plains hard winter wheat

Abstract: Wheat genotypes that efficiently capture and convert available soil nitrogen into harvested grain protein are key to sustainably meeting the rising global demand for grain protein. The purposes of this study were: to characterize the genetic variation for nitrogen use efficiency (NUE) traits within hard winter wheat adapted to the Great Plains of the United States and evaluate trends in the germplasm with year of release; to explore relationships among traits that may be used for selection within breeding prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 50 publications
(70 reference statements)
9
75
0
Order By: Relevance
“…This result is in agreement with those of Guttieri et al (2017). This result is in agreement with those of Guttieri et al (2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is in agreement with those of Guttieri et al (2017). This result is in agreement with those of Guttieri et al (2017).…”
Section: Discussionsupporting
confidence: 93%
“…The significant effect of the environment, observed in the current study, could be attributed to the difference in the soil conditions (i.e., texture, salinity, and pH) and the climate factors (i.e., temperature and relative humidity) that might affect the productivity of wheat genotypes (Shimelis and Laing, 2012). For instance, Guttieri et al (2017) evaluated a panel of 299 hard winter wheat genotypes for GY and NUE under two N levels (low and moderate). The low GY observed in this study at low N supply across environments was expected and was reported previously in several other studies (Gaju et al, 2011;Cormier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, phenotyping became a major bottleneck and resource constraint on genome-wide association mapping [19]. Thus we focused our efforts and resources on conducting a time-consuming phenotyping for CMS using 2111 spring wheat accessions with publicly available 9K SNP marker data [85].…”
Section: Association Mappingmentioning
confidence: 99%
“…Recently, a genome-wide association analysis with high-density SNP markers was conducted in order to identify genomic regions that may be associated with NUE traits in Great Plains hard winter wheat germplasm [35]. Interestingly, it was found that SNP markers on the long arm of a 2D chromosome were associated with NUE traits, in the same distal position where GS2 genes map.…”
Section: Gs2 Allelic Variants and Relationship With Gpcmentioning
confidence: 99%